Use of Zephyr stent in congenital heart diseases: A single-center study - Sudipta Bandyopadhyay; Muthukumaran Chinnaswamy Sivaprakasam (Wolters Kluwer Medknow Publications, 2023)
Large vessel stenosis is currently successfully treated with percutaneous stent implantation. Zephyr stent is a cobalt-chromium peripheral stent specifically designed for large-vessel stenting. Its specific "S-" and "C-" shaped flexible polylinks prevent stent foreshortening and recoil. We report our experience of using Zephyr among the pediatric population and their medium-term outcome. The study included a total of 19 patients treated with 21 Zephyr stents. The indications for stenting included coarctation of the aorta (four patients), stenosed pulmonary artery (eight patients), stenosed right ventricular outflow tract (five patients) or conduit (one patient), and percutaneous Fontan (one patient). All the procedures were successful. None of the patients showed any stent-related complications. Stent fractures, foreshortening, or recoil were not seen during follow-up. Our medium-term (1-20 months) follow-up showed a favorable outcome. One patient developed restenosis. Zephyr stent is a good therapeutic option for large-vessel stenting. However, it needs large-scale studies for further confirmation.